The study of available techniques for existing requirements engineering challenges based on literature review evidences - Besrour, S. (Maxwell Science Publications, 2014)
It is well known that software engineering suffer from various challenges. Moreover, numerous researchers found that project challenges have a negative effect on project time cost and user satisfaction. Additionally, Numerous Requirements Engineering (RE) methods have been proposed to improve the quality of requirements documents and to increase customer satisfaction about final product. Nevertheless, the choosing between various techniques may be confusing and puzzling. Therefore, this study aims to present, Literature review based study to link between RE challenges and available techniques to eliminate challenges using the utmost appropriate technique. Study conclusions are relevant for both industry and academic researchers in order to achieve effective software requirement engineering. Â© Maxwell Scientific Organization, 2014.